The use of equilibrium thermodynamic models for the prediction of inorganic phase changes in the co-firing of wheat straw with El Cerrejon coal. Issue 3 (June 2019) - Xing, P.; Darvell, L.I.; Jones, J.M.; Ma, L.; Pourkashanian, M.; Szuhánszki, J.; Williams, A.
Abstract: The combustion of pulverised coal in power stations results in slagging and fouling in the boiler section and this can be a more severe problem when co-fired with biomass, especially straw. Prediction of the effects of different combination of biomass and coal are helpful to the plant operators. Predictive software gives information about the onset and nature of the slag formed but often the results of these calculations have to be validated. This was undertaken in this work which gave a comparison of ash behaviour for coal (El Cerrejon) and wheat straw blends studied by ash fusion test, X-ray diffraction (XRD) and by using predictive software (FactSage). Ash prepared in the laboratory was also compared with ash produced in a 250 kW pilot-scale test furnace. The FactSage model showed good agreements with XRD data for the presence of inorganic phases with temperature, although it predicted some inorganic phases which are not detected in the XRD, particularly in low temperature ashes. Nevertheless, FactSage gave insight into liquid phase formation, more so than the ash fusion test, since it predicted the beginning of slag formation below the initial deformation temperature seen in the ash fusion test. For the coal, wheat straw and their blends, FactSage always predicted that slag formation is near to completion by the flow temperature observed in the ash fusion test. Highlights: X-ray diffraction used to analysis ash from El Cerrajon coal, straw and mixtures. Ash melting behaviour of different coal-straw blends assessed via laboratory methods. Slagging indices tested for El Cerrajon coal-straw blends. Thermodynamic modelling by FactSage usefully predicts slag formation.